Cost-benefit analysis of enhanced recovery after hepatectomy in Chinese Han population. Issue 34 (August 2018) - Jing, Xiaolin; Zhang, Bingyuan; Xing, Shichao; Tian, Liqi; Wang, Xiufang; Zhou, Meng; Li, Jiangfeng
Abstract: Background: Enhanced recovery after surgery (ERAS) programs have been proved effective for enhancing the clinical healing rate and reducing hospitalization cost in most countries of the world. It's a multi-model approach that designed to optimize perioperative pathway, attenuate the surgical stress response, and decrease postoperative complications. Objective: The economic benefit from the application of ERAS to colorectal surgery has been demonstrated in China. However, such economic benefit of ERAS programs for hepatectomy hasn't been clarified yet. This study was carried out to explore the clinical efficacy and cost effectiveness of ERAS in Chinese Han population after hepatectomy. Methods: ERAS program was implemented in our department for hepatectomy in December 2016. In total, 79 consecutive patients after hepatectomy were chosen as ERAS group (ERAS protocol) in coming half year while 121 consecutive patients after hepatectomy were chosen as Pre-ERAS group (traditional protocol) in past half year. The operation time, intraoperative blood loss, length of hospital stay (LOS), complication, readmission, and hospitalization cost of 2 groups were compared. Results: The LOS of ERAS group was 5.81 ± 1.79 days, significantly shorter than that of Pre-ERAS group (8.06 ± 3.40 d) ( P  = .000). The operation time was 168.03 ± 46.20 minutes for ERAS group and 175.41 ± 64.64 minutes for Pre-ERAS group respectively ( P  = .417). The intraoperative blood loss was 166.58 ± 194.13 mL (ERAS group) and 205.45 ± 279.63 mL (Pre-ERAS group) ( P  = .293). It should be noted that the hospitalization cost of ERAS group was 51556.18 ± 8926.05 Yuan (7835.05 ± 1355.45 US dollars), significantly less than that of Pre-ERAS group 60554.66 ± 15615.31 Yuan (9202.56 ± 2371.24 US dollars) ( P  = .000). The application of ERAS effectively saved 8998.48 Yuan (1367.51 US dollars) for each patient. Conclusions: ERAS implementation for hepatectomy surgery is safe and feasible for Chinese Han population. It eventually enhanced the clinical healing rate. The benefits from such programs include a reduction of the LOS, complication, and readmission rates. So each patient has access to better medical service. It effectively relieved the financial burden of patients. The benefits from such programs include a reduction of the hospitalization cost, especially in medication cost. So each patient can afford the diseases.